ASSOCIATION OF KNOWLEDGE WITH EATING HABITS AND BODY MASS INDEX AS THE RISK FACTORS OF DIABETES MELLITUS IN MALANG - Natasha Halim, Angie; Zuhriyah, Lilik; Setijowati, Nanik (Universitas Brawijaya, 2023)
Diabetes mellitus in Indonesia, especially in Malang, is still common. Diabetes mellitus is characterized by an increased blood glucose levels and can cause complications in various organs. Risk factors for diabetes mellitus consist of modifiable and non-modifiable factors. The level of knowledge related to diabetes mellitus played a role in the prevention of disease complications. Poor eating habits and lack of physical activity can increase BMI and blood sugar levels. This study aimed to find a relationship between knowledge with eating habits and body mass index as risk factors for diabetes mellitus in Malang. This analytical observational study used a cross sectional study design. The sample in the study amounted to 212 individuals consisting of health cadres, village officials, internal staff of Brawijaya University, and the community who were in the environmental network of village officials and health cadres of Malang City. The research instruments used were DKQ-24 and the 2018 riskesdas eating habits modification questionnaire. The results showed that of the 212 respondents, most had moderate knowledge levels (n=156), moderate eating habits (n=124), and abnormal BMI (n=143). Data analysis showed that there was no relationship between knowledge about diabetes mellitus and eating habits (p=0.629), knowledge about diabetes mellitus and body mass index (p=0.709), eating habits and body mass index (p=0.401). The conclusion of this study is that there was no relationship between knowledge and eating habits and body mass index in Malang.